Cost-effectiveness of brentuximab vedotin plus chemotherapy as frontline treatment of stage III or IV classical Hodgkin lymphoma. (1st February 2019) - Delea, Thomas E.; Sharma, Arati; Grossman, Aaron; Eichten, Caitlin; Fenton, Keenan; Josephson, Neil; Richhariya, Akshara; Moskowitz, Alison J.
Abstract: Objective: The ECHELON-1 trial demonstrated efficacy and safety of brentuximab vedotin plus doxorubicin, vinblastine, and dacarbazine (A + AVD) vs doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) as frontline therapy for stage III/IV classical Hodgkin lymphoma. This analysis evaluated the cost-effectiveness of A + AVD from a US healthcare payer perspective. Methods: The incremental cost-effectiveness ratio (ICER), defined as the incremental costs per quality-adjusted life year (QALY) gained, was estimated using a non-homogenous semi-Markov cohort model with health states defined on progression following frontline treatment, and for those with progression, receipt of autologous stem-cell transplant (ASCT), and progression after ASCT. Patients undergoing ASCT were classified as refractory or relapsed based on timing of progression. Probabilities of progression/death with frontline therapy were based on parametric survival distributions fit to data on modified progression-free survival (mPFS) from ECHELON-1. Duration of frontline treatment and incidence of adverse events were from ECHELON-1. Utility values for patients in the frontline mPFS state were based on EQ-5D data from ECHELON-1. Other inputs were from published sources. A lifetime time horizon was used. Costs and QALYs were discounted at 3%. Analyses were conducted alternately using data on mPFS for the overall and North American populations of ECHELON-1. Results: The ICER for A + AVD vs ABVD was 172, 074/QALY gained in the analysis using data on mPFS for the overall population and 69, 442/QALY gained in the analysis using data on mPFS for the North American population of ECHELON-1. The ICER is sensitive to estimated costs of ASCT and frontline failure. Conclusion: The ICER for A + AVD vs ABVD based on ECHELON-1 is within the range of threshold values for cost-effectiveness in the US. A + AVD is, therefore, likely to be a cost-effective frontline therapy for patients with stage III/IV classical Hodgkin lymphoma from a US healthcare payer perspective. Trial registration: ClinicalTrials.gov identifier: NCT01712490.